Modelling the errors in areal interpolation between zonal systems by Monte Carlo simulation. - Fisher, P. F.; Langford, M. (Environment & Planning A, 1995)
A Monte Carlo simulation method based on modifiable areal units is used to compare the results of interpolation—the transfer of data from one zonation of a region to another, where the two zonations are geographically incompatible—and to assess the errors that arise with interpolation. The Monte Carlo simulation method permits multiple interpolations of populations to be carried out from a single set of source zones to numerous sets of target zones. As a result, the properties of the full error distribution associated with a particular interpolation model can be examined. The method based on dasymetric mapping consistently provided the highest accuracy of those tested, whereas the areal weighting method provided the lowest accuracy.